TOURISTS PERFORMING THE UNPREDICTABLE: THE INFLUENCE OF THE SCRIPT, STAGE AND SOCIAL INTERACTION ON NORTHERN LIGHTS ACTIVITIES IN NORTHERN NORWAY - Wentzlaff, Franziska (UiT The Arctic University of Norway, 2015)
Visitors travel from all over the world to Northern Norway to view the natural spectacle, the Aurora Borealis or Northern Lights during the wintertime. To increase the chances of visitors viewing the lights, they participate in a range of different activities. In order to get an understanding of how tourists perform during those activities, an ethnographic methodology informed by feministic research values was applied. Data were gathered from different ethnographic methods and thematic analysis was used to categorize gathered data into the script, stage and sharing of performances. The findings indicate that northern light experiences are a fluent process of confrontation, adjustment and improvisation. The script behind Northern Lights experiences enables the participants to perform unknown activities in unfamiliar environments. Often, performance is a process of fluidly transiting from initially perceived uncontrolled situations to the actual performance of the activity. The uncertainty of the phenomenon Aurora Borealis requires improvisation and flexibility from all involved participants. Activities that are attached to such a place and setting associate with a need for increased improvisation, while flexible activities require additional guidance and structure. The stage for performance consists of the artic landscape and darkness both involving uncontrollable factors of the natural phenomena Northern Lights and the weather. Businesses use and form through materiality that supports performance, a controlled environment and stage within nature. The guide negotiates between stage, script and the visitors to enable their performance. Nevertheless, performance is individual and varies due to personal background and previous experiences. Sharing the experience with others and expressing themselves was almost as important for the tourists as to listen to the guide. Relatedly, performance does not just take place throughout a Northern Lights activity itself, additional performances reach and continue through social ...